Thermal effects of prenatal doppler ultrasound on newborns of oryctolagus cuniculus - Umi Nadrah Amran (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Despite the usefulness of Doppler ultrasound in complementing prenatal care, its usage had also been reported to increase the temperature of tissues. Prolonged exposure to Doppler ultrasound may increase the risk of bioeffects. Therefore, the aim of this study was to investigate the influence of Doppler ultrasound on the body weight, brain size and bone mineral density (BMD) of newborn Oryctolagus cuniculus throughout three gestational ages (GA). The study utilised twelve (12) pregnant Oryctolagus cuniculus or New Zealand white rabbits (NZWR) (Control Group = 3; Exposed Group = 9). By utilizing Siemens Model ACUSON X150 ultrasound machine, linear array transducer VF10-5 (5.0 to 10.0 MHz) the exposed group was exposed once to Doppler ultrasound at a stipulated gestational day (GD) of their GAs (1st GA, GD 8-9; 2nd GA, GD 18-19; 3rd GA, GD 29-30). They were exposed to three different Doppler ultrasound exposure durations (ED) (30, 60 and 90 minutes). Acoustic output parameters such as frequency = 5.2 MHz, focal distance = 4.5 cm, Db/DR = 55/50 and mechanical index = 0.7 - 1.0 were kept constant. A total of 64 newborns (control, n = 17; 30 minutes ED, n = 17; 60 minutes ED, n = 12; 90 minutes ED, n = 18) were analysed for body weight, brain size and BMD measurements. The data were statistically analysed using Statistical Package for Social Sciences (SPSS) version 20. In the newborn's body weight, significant differences were perceived for 1st GA (p = <0.01) and 2nd GA (p = 0.02). No significant correlations were found for all GAs. For the newborn's brain size, significant correlation was found for 1st GA (brain surface, r = -0.44; brain volume, r = -0.42) and 2nd GA (brain surface, r = -0.57; brain volume, r = -0.52) only. Significant differences were also found for 1st GA (brain surface, p = <0.01; brain volume, p = <0.01 and 2nd GA (brain surface, p = <0.01; brain volume, p = 0.01). In terms of BMD, significant correlation was found for all GAs (1st, r = 0.47; 2nd, r = -0.64; 3rd, r = 0.50) but significant differences were only found in BMD for 2nd GA (p = 0.01), and 3rd GA (p = 0.02). In conclusion, the results highlighted the heating effects of Doppler ultrasound on Oryctolagus cuniculus newborns with respect to body weight and brain size in early GAs (1st & 2nd), whereas BMD in later GAs (2nd & 3rd). The study could suggest that Doppler ultrasound ED should be limited to 30 minutes as significant results were observed in all GAs in order to reduce the potential heating effects on the newborns. The findings presented in this thesis fortified the understanding on the heating effects of Doppler ultrasound besides facilitating the establishment of guidelines on using Doppler ultrasound safely in the future.